DOI: 10.17077/etd.lav4h3g0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between career decision self-efficacy, ethnic identity, and academic self-concept and achievement of African American high school students

Abstract: To my husband Rohman, your unconditional love, support, and sacrifices helped to make this dream possible. I love you more than words can express. Justice departments, thank you for all of your encouragement and support. Lastly, I would like to thank all of the Chicago area Upward Bound programs for allowing me to conduct research with students in your programs, along with the students and parents for agreeing to participate in this research study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 132 publications
(276 reference statements)
0
3
0
1
Order By: Relevance
“…This was attributed to pressure of competing roles on both teachers and students, which increased their workload. Thus, irregular career guidance and counselling programmes in schools denied students benefits associated with timely and continuous career guidance and counselling such as increased self-awareness, self-confidence, career identity and career maturity as suggested by Hooley and Rice (2019) and Bounds (2013). Anghel and Gati (2019) and Maree and Che (2020) observed that delayed career guidance and counselling contributed to career indecision among students, of which secondary schools in Uganda may need to be mindful.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to pressure of competing roles on both teachers and students, which increased their workload. Thus, irregular career guidance and counselling programmes in schools denied students benefits associated with timely and continuous career guidance and counselling such as increased self-awareness, self-confidence, career identity and career maturity as suggested by Hooley and Rice (2019) and Bounds (2013). Anghel and Gati (2019) and Maree and Che (2020) observed that delayed career guidance and counselling contributed to career indecision among students, of which secondary schools in Uganda may need to be mindful.…”
Section: Discussionmentioning
confidence: 99%
“…It includes knowledge of positive self-concept that covers areas of gender self-awareness, mental health, professional knowledge, and social influence of parents, friends, and teachers (Amani, 2013;Cortes & pan, 2017). It also covers understanding of the role of other factors that influence students' self-awareness like culture, family, politics, social affairs, and economics (Chinyamurindi, 2016;Chand et al, 2014;Sheri et al, 2013). According to Super (1976) self-awareness is a cognitive task that progresses through life span.…”
Section: Self-knowledgementioning
confidence: 99%
“…Siswa secara aktif berperan dalam proses belajar sehingga berhasil mencapai keberhasilan dalam prestasi akademik, yang merefleksikan adanya konsep diri akademik yang tinggi dalam diri siswa (Zimmerman, dalam Ordaz-Villegas, Acle-Tomasini, & Reyes-Lagunes, 2013). Bila seseorang memiliki konsep diri yang positif maka keyakinan dirinya dalam mengambil keputusan karier juga meningkat (Bounds, 2013). Lebih lanjut, Bong & Skaalvik (2003) menjelaskan bahwa siswa yang memiliki konsep diri akademik yang positif akan terdorong untuk lebih terlibat dalam kegiatan akademik dan penetapan tujuan pendidikan, menunjukkan usaha dan ketekunan dalam belajar, menunjukkan performa dan prestasi akademik yang baik serta lebih terlibat dalam proses pengambilan keputusan karier.…”
Section: Pendahuluanunclassified